2012
DOI: 10.1186/1939-8433-5-20
|View full text |Cite
|
Sign up to set email alerts
|

Specific patterns of genetic diversity among aromatic rice varieties in Myanmar

Abstract: BackgroundAfter observing peculiar rice varieties in Myanmar, in terms of classification in varietal groups and of grain quality, we focused on Myanmar varieties and analyzed variations at 19 microsatellite loci as well as sequences of the aroma gene BADH2.ResultsMicrosatellites were able to retrieve the well-established classification into Indica (isozyme group 1), Japonica (group 6, comprising temperate and tropical forms) and specific groups from the Himalayan foothills including some Aus varieties (group 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
1
17
1
Order By: Relevance
“…The numbers of alleles detected in this study are comparable to those observed by [18] using Basmati and non-Basmati rice varieties from Pakistan which had allelic richness of 2-4 alleles with an average of 2.75 alleles per SSR locus. In contrast, the average number of alleles detected in this study was comparatively higher than the values obtained using Indian aromatic rice varieties which had an average of 2.08 and 2.5 alleles per locus [19] and [5]. The average number of alleles per locus detected in this study was lower than the values obtained using a different set of rice germplasm from India, Portugal and Venezuela which had 4.5, 7.7 and 13.0 alleles per locus for various classes of SSR markers [20][21][22].…”
Section: Resultscontrasting
confidence: 82%
See 1 more Smart Citation
“…The numbers of alleles detected in this study are comparable to those observed by [18] using Basmati and non-Basmati rice varieties from Pakistan which had allelic richness of 2-4 alleles with an average of 2.75 alleles per SSR locus. In contrast, the average number of alleles detected in this study was comparatively higher than the values obtained using Indian aromatic rice varieties which had an average of 2.08 and 2.5 alleles per locus [19] and [5]. The average number of alleles per locus detected in this study was lower than the values obtained using a different set of rice germplasm from India, Portugal and Venezuela which had 4.5, 7.7 and 13.0 alleles per locus for various classes of SSR markers [20][21][22].…”
Section: Resultscontrasting
confidence: 82%
“…Therefore, characterization and varietal identification of available landraces and improved varieties have become important in modern day crop improvement [4]. There are more than 100,000 rice varieties worldwide but the major categories include; indica, japonica, basmati and glutinous [5]. This study was carried out using 13 randomly selected rice landraces and improved varieties largely grown in Kenya and Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the loss of function of BADH2 allows an accumulation of the precursor and triggers the synthesis of 2-AP (Bradbury et al 2008a), and thus several haplotypes have been identified based on SNP (Jin et al 2003) and microsatellite markers associated with loss of BADH2 function (Cordeiro et al 2002). Studies have mapped insertions, deletions, and polymorphisms resulting in the discovery of multiple alleles of badh2 across the different subpopulations of rice (Amarawathi et al 2008;Bourgis et al 2008;Bradbury et al 2005;Kovach et al 2009;Myint et al 2012;Niu et al 2008;Shao et al 2011;Shi et al 2008). Studies have mapped insertions, deletions, and polymorphisms resulting in the discovery of multiple alleles of badh2 across the different subpopulations of rice (Amarawathi et al 2008;Bourgis et al 2008;Bradbury et al 2005;Kovach et al 2009;Myint et al 2012;Niu et al 2008;Shao et al 2011;Shi et al 2008).…”
Section: Genetic Variations In Rice Grain Aroma and Its Contribution mentioning
confidence: 99%
“…Naturally, genetic diversity within species can be identified using microsatellite DNA in fragrance rice [2][3][4][5][6][7][8][9][10], also identification of germplasm collection of basmati rice cultivar from India, they are genetic variability among these cultivars [11][12][13]. According to myint et al, [14] that Myanmar's aromatic rice difference with indica or japonica type and Badh2 allele showed three base pair insertion.…”
Section: Introduction mentioning
confidence: 99%
“…Several molecular markers can be used for identification of genes linked to fragrance in rice [12], such as SSR markers [5][6][7][8][9][10][11][12][13][14][15]. The DNA marker reported by Bradburry et al [21] can clearly show the difference between aromatic rice and non-aromatic rice, but fails to differentiate the Indonesian local aromatic rice variety derived from cv.…”
Section: Introduction mentioning
confidence: 99%